The Relevance of Sales Growth, Profitability, And Capital Structure in The Valuation of Firm Value In The Modern Era - Ariffianto, Raufha; Takarini, Nurjanti (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The purpose of this study is to determine how much firm value in coal subsector companies listed on the Indonesia Stock Exchange is influenced by factors such as sales growth, profitability, and capital structure for the 2020–2023 period. 41 coal subsector companies listed on the Indonesia Stock Exchange for the 2020–2023 period made up the population of this study, and there were 26 companies in total in the research sample. Purposive sampling was the technique used to collect the data. Using SPSS 25 software, the multiple linear regression analysis method was used to analyze the data. The study's findings indicate that: 1) Sales Growth positively and significantly affects Firm Value; 2) Profitability positively and significantly affects Firm Value; and 3) Capital Structure positively and significantly affects Firm Value.